Numerical integration of the process of cooling gas formed by thermal recycling of waste - Vambol, Viola (Eastern-European Journal of Enterprise Technologies, 2016)
The present paper describes the results of a numerical integration of the process of cooling gas during thermal recycling of waste. The physical model of such cooling is based on injecting the cooling liquid by centrifugal nozzles. The research object is gas-dynamic interphase interactions in the evaporative heat exchanger. The purpose of the research is to improve the ecological safety of thermal recycling of waste by preventing the formation of highly toxic substances in the generated gas. The mathematical models of the gas and dispersed phases are developed and the mathematical description of the interphase interactions in the heat exchanger is provided on the basis of laws of conserving the weight and the impulse amount in an environment that is inhomogeneous in terms of the composition and phases and includes the generated gas, drops of water, and steam. The mathematical formulation of the conservation laws for viscous gas (steam) is achieved through the Navier-Stokes equations; for drops, it is given as an equation of the balance of forces that affect the drop and equalize the inertia force and the resultant forces of gravity and aerodynamic resistance. The studied computational area covers a space fragment bounded by the walls of the heat exchanger. It has been scientifically proved that such technological equipment can be used to provide a sharp cooling of flue gases. The mode of fast cooling prevents the creation of temperature conditions that would facilitate dioxins formation, and thus it increases ecological safety.